UJI AKTIVITAS ANTIBAKTERI DARI EKSTRAK ETANOL DAUN MANGKOKAN (Polyscias Scutellaria) TERHADAP BAKTERI Bacillus cereus DAN Shigella dysentriae - Sri Hainil; Rury Trisa Utami; Delladari Mayefis; Nurul Asiqin (Nusantara Hasana Journal, 2025)
Mangkokan leaves (Polyscias scutellaria) are medicinal plants believed to treat the digestive tract, such as diarrhea, and abdominal pain, to use it by drinking a decoction of Mangkokan leaves as a traditional medicine. This study aims to determine the antibacterial activity of ethanol extract of Polyscias scutellaria leaves in inhibiting the growth of Bacillus cereus and Shigella dysentriae bacteria. The active compounds in Mangkokan leaves contain alkaloids, saponins, phenolics, and steroids. These ingredients can function as antibacterial. This study was carried out by maceration method using 96% ethanol solvent, and the viscous extract obtained tested to see the inhibition in Bacillus cereus and Shigella dysenteriae bacteria using the disc paper diffusion method with concentrations of 25%, 50%, 75%, and 100%. The positive control was chloramphenicol 30 μg/disk, and the negative control was DMSO 5% (Dimethylsulfoxide). The test results showed that Mangkokan leaf ethanol extract had antibacterial activity against Bacillus cereus bacteria with a (moderate) inhibitory response at a concentration of 100% of 7.96 mm. In comparison, Shigella dysentriae has an inhibitory response (moderate) at a concentration of 100% of 7.68 mm